EFFECT OF HORMONE REPLACEMENT THERAPY ON PATELLA CARTILAGE VOLUME - Özlem Baysal; Zühal E Altay; Tülay Öner; Tamer Baysal; Feza Burak; Saim Yoloğlu (Archives of Rheumatology, 2005)
It has been shown that symptomatic knee osteoarthritis (OA) may often be related to patellofemoral OA. Patellofemoral OA is more common in women than men, suggesting that differences in sex hormones may modulate the disease. Although some epidemiological data suggests that hormone replacement therapy (HRT) has an effect on the incidence and prevalence of OA in postmenopausal women, little is known about the effect on patellofemoral OA. In this study, our aim was to determine the effect of HRT on patellar cartilage volumes in postmenopausal non HRT user (control group) and HRT user women. The patellar cartilage volumes of 23 non HRT user women (control group) and 21 HRT user women (less than 5 years), 15 HRT user women (more than 5 years) were calculated by means of magnetic resonance imaging (MRI). Statistical difference was found between the patellar cartilage volume measurement of HRT user ( > 5 years) and non-user postmenopausal women (p=0.001). The data in this study indicates that especially long term HRT may have preventive effect on the patellar cartilage.